2021
DOI: 10.1186/s12951-021-00969-3
|View full text |Cite
|
Sign up to set email alerts
|

Directional homing of glycosylation-modified bone marrow mesenchymal stem cells for bone defect repair

Abstract: Background One of the greatest challenges for tissue-engineered bone is the low survival rate of locally grafted cells. The cell homing technology can effectively increase the number of these grafted cells, therefore, enhancing the repair of bone defects. Here we explore the effect of fucosylation modification on the directional homing of bone marrow mesenchymal stem cells (BMSCs) and their ability to repair bone defects. Results Glycosylated BMSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…First, they can secrete a variety of soluble factors, including cytokines, growth factors and chemokines as well as immunomodulatory molecules, which participate in regulating proliferation, apoptosis, fibrosis and immune regulation of damaged tissues. In addition, BMSCs can also home to the damaged tissue and differentiate into specific cells to reconstruct the damaged local microenvironment, so as to maintain the integrity of tissue morphology and function stability ( 35 , 45 47 ).…”
Section: Biological Characteristics Of Bmscsmentioning
confidence: 99%
“…First, they can secrete a variety of soluble factors, including cytokines, growth factors and chemokines as well as immunomodulatory molecules, which participate in regulating proliferation, apoptosis, fibrosis and immune regulation of damaged tissues. In addition, BMSCs can also home to the damaged tissue and differentiate into specific cells to reconstruct the damaged local microenvironment, so as to maintain the integrity of tissue morphology and function stability ( 35 , 45 47 ).…”
Section: Biological Characteristics Of Bmscsmentioning
confidence: 99%
“…To overcome these limitations, in situ tissue regeneration technology has been designed, which utilizes the implantation of bioactive scaffolds to recruit host progenitor cells, and simultaneously provides optimal microenvironment, contributing to proliferation and differentiation of recruited cells, finally promoting tissue regeneration ( Lutolf et al, 2009 ; Ko et al, 2013 ). Several studies have confirmed the superiority of MSCs homing in improving the quantity and efficacy of regeneration of different tissues ( Karp and Leng Teo, 2009 ; Xiang et al, 2020 ; Chen et al, 2021 ). For instance, Wang succeeded in BMSCs recruitment and osteogenic differentiation by loading hydroxyapatite/polyacrylonitrile scaffolds with SDF-1 ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 94%
“…Bone repair requires multiple cytokines and signaling pathways that are involved in a complex and sequential process. 9 A bone defect is repaired in three sequential stages: inflammation, bone scab healing, and remodeling. 10 The most critical cells during the entire process are the mesenchymal stem cells (MSCs), which secrete a large number of cytokines and proliferate and differentiate into osteoblasts that form fibrous bone scabs.…”
Section: Introductionmentioning
confidence: 99%